Desvendando os sentidos do gênero discursivo charge através da prática de leitura em sala de aula - Cruz , Lucélia de Albuquerque Melo (2020)
The practice of reading in the classroom is determined by the National Common Curricular Base (BNCC) of Portuguese Language which considers the text as the center of the language practices, including the multimodal genres that are common nowadays. Therefore, we realized the students' preference for these texts, especially, the texts who associate criticism with humor, such as cartoons. However, when the students read, we were sure that they were limited to the perception of explicit information, impairing the process of attributing meanings. Thus, the objective of this work is to contribute to the development of the reading competence of the discursive genre cartoon, through the implementation of reading workshops that approach some skills indicated by the descriptors of the SAEB/Prova Brasil Reference Matrix. Therefore, we used as theoretical reference the reading conceptions presented by Solé (1998), Menegassi (2010) and Bonifácio (2015), as well as, the theoretical contributions given by Koch & Elias (2017) and Cavalcante (2011) about reading process and discursive genres, also seen from the Bakhtin´s perspective (2003). In addition, we sought support in official documents, such as PCN (BRASIL, 1998), BNCC (BRASIL, 2017) and PDE/Prova Brasil (BRASIL, 2011). Regarding the cartoon, we sought support, mainly, in Romualdo (2000) and in other researchers who showed interest in the study of this genre. About the methodology, we developed an action research, characterized by a qualitative and quantitative approach, of a descriptive and interventionist character and an applied nature. Thus, the corpus was constituted by the selection of many questions of the diagnostic activities answered by the students of the 9th grade of a municipal school located in Santa Rita-PB. The intervention proposal consisted of the following stages: initial diagnostic activity, reading workshops, that ended with a visit to Régis Soares's Atelier to learn about the Charges na Rua Project and final diagnostic activity. At the end of the application, we realized that the results were satisfactory, not only to the measurement of the numerical data, but also verify to the change in the posture of the students who, from the reading workshops, began to see the cartoon as an important text for the dissemination. from criticism to different segments of our society.